IgG‐mediated down‐regulation of IgE bound to mast cells: a potential novel mechanism of allergen‐specific desensitization. Issue 3 (19th December 2013) - Uermösi, C.; Zabel, F.; Manolova, V.; Bauer, M.; Beerli, R. R.; Senti, G.; Kündig, T. M.; Saudan, P.; Bachmann, M. F.
Abstract Background Allergen‐specific IgGs are known to inhibit IgE‐mediated mast cell degranulation by two mechanisms, allergen‐neutralization and engagement of the inhibitory FcγRIIB recruiting the phosphatase SHIP‐1. Here we unravel an additional mechanism of IgG‐mediated mast cell desensitization in mice: down‐regulation of allergen‐specific IgE. Methods Mast cells were loaded in vitro and in vivo with monoclonal IgE antibodies specific for Fel d1 and exposed to immune complexes consisting of Fel d1‐specific IgG antibodies recognizing different epitopes. Down regulation of IgE was followed by flow cytometry. Results Mast cells loaded with 2 different IgE antibodies efficiently internalized the IgE antibodies if exposed to recombinant Feld d1. In contrast, no down‐regulation occurred if mast cells were loaded with IgE antibodies exhibiting a single were before stimulation with recombinant Fel d1. Interestingly, however, IgEs of a single specificity were rapidly down‐regulated in vitro and in vivo in the presence of Fel d1‐specific monoclonal IgGs recognizing another epitope on Fel d1. Despite FceRI‐internalization, little calcium flux or mast cell degranulation occurred. FcγRIIB played a dual role in the process since it enhanced IgE internalization and prevented cellular activation as documented by the inhibited calcium flux and mast cell degranulation. Similar observations were made in the presence of low concentrations of IgEs recognizing several epitopes on Fel d1. Conclusion We demonstrate here that Fel d1‐specific IgG antibodies interact with FcγRIIB which (i) promotes IgE internalization; and (ii) inhibits mast cell activation. These results broaden our understanding of allergen‐specific desensitization and may provide a mechanism for long‐term desensitization of mast cells by selective removal of long‐lived IgE antibodies on mast cells.